(untitled) (Research, Society and Development, 2022)
The objective was to determine the prevalence of multidrug-resistant bacteria in patients admitted to an intensive care unit (ICU) of a private hospital in western Paraná. Patients aged 18 years or older, admitted between January 1, 2021 and December 31, 2021 were included. Clinical materials used were: rectal swab, nasal swab, tracheal secretion, urine, central venous catheter tip and peripheral blood culture. Males had a higher rate of bacterial infections, with tracheal secretion being the analyzed sample that showed the highest prevalence of Klebsiella pneumoniae. As for antimicrobials, many patients showed resistance to all antimicrobials, those with the lowest rate of resistance were carbapenems. It is extremely important to know the prevalence of multidrug-resistant bacteria, as the treatment of bacterial infections in the ICU is a major problem for public health not only in Brazil, but worldwide.